Understanding the Air Force's capability to effectively apply advanced distributed simulation for analysis : an interim report - Kerchner, Robert; Friel, John A.; Lucas, Thomas W.; Project Air Force (U.S.). Force Modernization and Employment Program; Rand Corporation; United States. Air Force (Santa Monica, CA : RAND, 1996)
This report identifies major advantages and challenges of using advanced distributed simulation (ADS) in Air Force analysis, training, and mission rehearsal. As part of a carefully designed analytic plan, ADS could improve presentation of results, allow for parallel processing, and achieve faster model development. The report recommends that the Air Force develop an investment strategy and a comprehensive plan to implement ADS improvements.
Includes bibliographical references (p. 65-66).
Also available on the internet via WWW in PDF format.
Keywords: Aeronautics, Military -- United States -- Data processing; Electronic data processing -- Distributed processing; Interactive computer systems